Slim Fit Coaching System For Kelab Sihat Pekan - Siti Nor Aisyah, Mohamad (2023)
Nowadays, health is the top priority of everyone. To gain the ideal weight, nutritious food intake as well as adequate exercise can help keep a person reaching the ideal weight. Now, most people rarely exercise due to lack of time due to work, there are also those who are not interested in sports, age factors and others. However, to achieve the ideal weight, it is not only exercise that helps. Even the right food intake according to the needs of one's body is also important to gain the ideal weight. So, the purpose of this project is to provide a platform to the community to achieve the ideal weight. As a result, all who participate will gain ideal weight and good health as a result of the Kelab Sihat Pekan coach’s guidance. These results are important in achieving the objectives of the project.